2014
DOI: 10.2136/sssaj2014.07.0291
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Runoff Water Quality as Affected by Broiler‐Litter Application to a Udult in the Ozark Highlands

Abstract: Repeated annual land application of organic soil amendments, such as broiler litter (BL), to managed grasslands for increased forage yields has increased concerns about potential surface water contamination from runoff. Furthermore, water quality concerns are exacerbated in areas of underlying karst, such as the Ozark Highlands, where runoff can rapidly enter the groundwater system. Therefore, the objective of this study was to determine 8‐yr (May 2003–April 2011) linear trends in annual runoff water quality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The BL used in this study had a similar composition to that used in previous studies in Arkansas (Adams et al, 1994), New York (Brock et al, 2007), Pennsylvania (Kleinman et al, 2002), and overseas in Nigeria (Agele et al, 2004). As reported by McMullen et al (2014a), and as would be expected, annual aboveground dry matter production was consistently greater as a result of BL additions compared with the unamended control.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The BL used in this study had a similar composition to that used in previous studies in Arkansas (Adams et al, 1994), New York (Brock et al, 2007), Pennsylvania (Kleinman et al, 2002), and overseas in Nigeria (Agele et al, 2004). As reported by McMullen et al (2014a), and as would be expected, annual aboveground dry matter production was consistently greater as a result of BL additions compared with the unamended control.…”
Section: Resultssupporting
confidence: 83%
“…It is likely that the BL-applied P remained concentrated near the soil surface in the litter treatments and consequently was more susceptible to runoff rather than leaching deeper into the soil profile. This contention is supported by the results of McMullen et al (2014a), who reported 8-yr cumulative runoff losses of PO 4 -P and total P to be more than three times greater from the litter treatments than from the unamended control. In addition, the added BL stimulated an aboveground biomass production difference among treatments (McMullen et al, 2014b), thus plant uptake of P probably further removed P from the soil profile to decrease the potential for P leaching.…”
Section: Flow-weighted Mean Concentrationsmentioning
confidence: 69%
See 1 more Smart Citation
“…Even if leachate P losses do not affect surface or groundwater quality short‐term, results indicate that karst‐derived soils are susceptible to deep soil profile leaching, which may increase P concentration of deeper soil layers and may serve as a source of P once remobilized (Sharpley et al., 2013). Further, the effects of elevated nutrient and trace metal concentration associated with litter application can affect surface and subsurface water quality long‐term even after the cessation of poultry litter application (McMullen, Brye, Daigh, et al., 2014; McMullen, Brye, Miller, et al., 2014; Menjoulet et al., 2009; Pirani et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…pastures in a subtropical environment in Australia (Lowe & Cudmore, 1978). As illustrated by McMullen et al (2014), repeated applications of broiler litter at high rates over extended periods of time can produce long-term risk of surface water contamination from runoff. Despite P buildup concerns, Sauer et al (2000) reported NO 3 -N loss was greater through nutrient runoff from broiler litter in a pasture environment than was P. Considering the options, the biological potential of slow-release N fertilizer sources such as the coated material evaluated have sufficient potential to justify efforts to develop economically viable products to provide the potential economic and environmental benefits for appropriate pasture systems.…”
Section: Discussionmentioning
confidence: 99%